Cities and Wetlands The Return of the Repressed in Nature and Culture - Giblett, Rod (Environmental Cultures, 2016)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. From New Orleans to New York, from London to Paris to Venice, many of the world's great cities were built on wetlands and swamps. Cities and Wetlands is the first book to explore the literary and cultural histories of these cities and their relationships to their environments and buried histories. Developing a ground-breaking new mode of psychoanalytic ecology and surveying a wide range of major cities in North America and Europe, ecocritic and activist Rod Giblett shows how the wetland origins of these cities haunt their later literature and culture and might prompt us to reconsider the relationship between human culture and the environment. Cities covered include: Berlin, Boston, Chicago, Hamburg, London, New Orleans, New York, Paris, St. Petersburg, Toronto, Venice and Washington.